Penguatan Pemahaman Fikih Wanita melalui Pendekatan Pembelajaran Kontekstual bagi Anak-Anak - Khoidah, Imro Atul; Wahyuni, Fitri; Masduki, Moh. (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to describe the implementation of contextual learning through the Ngaji Kitab Uyunul Masailinnisa' program and examine how this program strengthens the understanding and application of women's fiqh among sixth-grade female students at MI Al-Hikam. Many female students experience confusion in understanding basic laws regarding menstruation, postpartum bleeding, and istihadhah. This study employed a qualitative approach with field research design. Data collection was conducted through observation, in-depth interviews with teachers and students, and documentation of learning activities. Data analysis used reduction, presentation, and conclusion drawing techniques with descriptive qualitative methods. Data validity was obtained through source and method triangulation and member checking. The results showed that: (1) The implementation of contextual learning in strengthening women's fiqh understanding was carried out by applying seven main components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment; (2) The implementation of contextual learning in strengthening women's fiqh application at MI Al-Hikam was conducted through three activities: discussion, direct practice simulation, and reflection activities, which included modeling and reflection components; (3) The outcomes of the Uyunul Masailinnisa' program in strengthening women's fiqh understanding were evident from students' ability to differentiate terms of menstruation, postpartum bleeding, and istihadhah, understand the conditions and pillars of obligatory bathing, and develop curiosity and courage to ask questions. Meanwhile, the outcomes in strengthening women's fiqh application were visible from students beginning to record their menstrual cycles, maintain body hygiene during menstruation, avoid prohibited activities during impurity, and demonstrate modesty, shyness, and self-responsibility.